Speech assessment following microsurgical soft palate repair. Issue 3 (March 2023) - Bschorer, Frizzi; Hornig, Lena; Schön, Gerhard; Bschorer, Reinhard
Abstract: The aim of this study was to analyze speech intelligibility of children, who had undergone microsurgical soft palate repair according to Sommerlad. Cleft palate patients were treated by closure of the soft palate according to Sommerlad at about 6 months of age. At the age of 11, their speech was evaluated through automatic speech recognition. Word recognition rate (WR) was used as the outcome parameter of automatic speech recognition. To validate automatic speech results, an institute for speech therapy evaluated the speech samples for perceptual intelligibility. The results of this study group were compared to an age-matched control group. A total of 61 children were evaluated in this study, 29 in the study group and 32 in the control group. Study group patients had a lower word recognition rate (mean 43.03, SD 12.31) compared to the control group (mean 49.98, SD 12.54, p = 0.033). The magnitude of the difference was considered small (95% CI of the difference 0.6–13.3). The study group patients received significantly lower scores in the perceptual evaluation (mean 1.82, SD 0.58) compared to the control group mean (mean 1.51, SD 0.48, p = 0.028). Again, the magnitude of the difference was small (95% CI of the difference 0.03–0.57). Within the limitations of the study it seems that microsurgical soft palate repair according to Sommerlad at the age of 6 months might be a relevant alternative to other well established surgical techniques.